2015
DOI: 10.1037/tra0000068
|View full text |Cite
|
Sign up to set email alerts
|

Hispanic ethnicity and Caucasian race: Relations with posttraumatic stress disorder’s factor structure in clinic-referred youth.

Abstract: The severity of posttraumatic stress disorder (PTSD) symptoms is linked to race and ethnicity, albeit with contradictory findings (reviewed in Alcántara, Casement, & Lewis-Fernández, 2013; Pole, Gone, & Kulkarni, 2008). We systematically examined Caucasian (n = 3,767) versus non-Caucasian race (n = 2,824) and Hispanic (n = 2,395) versus non-Hispanic ethnicity (n = 3,853) as candidate moderators of PTSD's 5-factor model structural parameters (Elhai et al., 2013). The sample was drawn from the National Child Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 34 publications
3
23
0
Order By: Relevance
“…As university campuses become more ethnically diverse, Latinos are showing the fastest rate of enrollment growth [ 44 ]. Latinos have also shown a greater risk of developing PTSD [ 45 – 48 ] and may experience more severe symptoms [ 36 ]. While the disparity in PTSD among Latinos could be due to the inappropriate use of culturally insensitive measures, it could also be due to differences in culture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As university campuses become more ethnically diverse, Latinos are showing the fastest rate of enrollment growth [ 44 ]. Latinos have also shown a greater risk of developing PTSD [ 45 – 48 ] and may experience more severe symptoms [ 36 ]. While the disparity in PTSD among Latinos could be due to the inappropriate use of culturally insensitive measures, it could also be due to differences in culture.…”
Section: Introductionmentioning
confidence: 99%
“…Although measurement invariance on the IES-R has not been assessed with Latinos, research on other PTSD scales have found measurement invariance [ 48 ] and non-invariance [ 51 ] between Latino and Caucasian sub-samples. This inconsistency might be caused by study characteristics, such as the specific scale assessed in the study.…”
Section: Introductionmentioning
confidence: 99%
“…Charak et al (2014) found that the Dysphoric Arousal Model of PTSD assessed by the PCL-C was the best model in an Indian sample, although the fit indices of all PTSD models were fairly similar, which underlines the cross-cultural validity of PTSD symptomatology. In a study by Contractor et al (2015), the structural invariance of PTSD 5-factor model across Hispanic and Caucasian groups was supported.…”
Section: Introductionmentioning
confidence: 90%
“…Only when MI holds for a mental health questionnaire, cross-group differences in scores on mental health constructs are meaningful (Meredith, 1993; Steenkamp & Baumgartner, 1998; Van De Schoot et al, 2012). Methodologically, scholars have examined MI of mental health questionnaires using confirmatory factor analyses (CFA; Charak et al, 2014; Contractor et al, 2015; Fodor et al, 2015; Schnyder et al, 2015). CFA is a widely-used technique for testing MI of mental health questionnaires.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to meaningfully compare the prevalence of PTSD rates among African Americans with that among members of other ethnic groups 11 and accurately interpret cultural correlates of observed group differences, it is necessary to first establish the factorial structure and external validity of PTSD factor scores among African Americans. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%